CLASSIFICATION OF WORKS BY DEFINITION OF VERBS (Archive of Conferences, 2020)
The verb as an object of linguistic research is a topic that constantly attracts the attention of researchers. This circumstance is explained by the important role that verbs play in the language system. It is known that a verb in Arabic, by its semantics, conveys an action or state of a person or an object and acts as a predicate in a sentence